Pengembangan Fungsi Persimpangan/Nodes pada Kawasan Perdagangan dan Jasa Pasar Pagi Kota Samarinda melalui Penerapan Desain Shared Street Space - Enrico Vincensius Yudistira Harryanto; Gian Sapherd Laibahas (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2025)
Node or intersection is one aspect in the theory of city image that functions as a point of intersection of urban paths or lanes. There is one potential intersection point in the Morning Market Commercial Area, one of the commercial areas in Samarinda City. The lack of parking space and irregular vehicles parked on the shoulder of the road disrupt traffic around the market and interfere with pedestrian space. Based on the existing conditions that have intersection points, a shared street space design is offered which is a concept approach to spatial design on the road to minimise the differences between vehicle movement, cyclists, and pedestrians. This application is intended to develop the function of the Morning Market intersection to create harmony for road users through analysis of image elements, land figures and elements of urban area design, context, structure and interrelationships of the area and environmental conditions such as sun, wind, visibility and visual quality with mapping and descriptive. The synthesis results are formulated descriptively into principles, elements and visual designs and are equipped with literature studies related to shared street space design aspects.